Utilization of Internet of Things (IoT) for Biometrics Attendance and Web-Based Student Monitoring - Sidik, Achmad; Sunggono, Nova Teguh; Stianingsih, Lilis; Sidiq, Yusuf Alimun (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
SMPN 31 Tangerang aims to enhance the accuracy and efficiency of its student attendance system. The current problem is that the existing attendance system is easy to manipulate and lacks accuracy. This research aims to develop a biometric attendance system based on fingerprint technology to address these issues, with output presented in a web page format and without using paper. The methods used in this study include literature review, interviews, and observations for data collection. Development methods involve system design and the waterfall model. The developed attendance system utilizes IoT (Internet of Things) technology and electronic circuits to facilitate implementation and use. The research results show that the biometric fingerprint attendance system can improve student discipline. The system allows for attendance monitoring through a web interface, with data that can be backed up to Microsoft Excel. This device offers high accuracy, good attendance speed, and ease of use for students. In conclusion, the implementation of the biometric attendance system and web-based monitoring meets the school's needs for efficient and effective attendance management and monitoring.